1997
DOI: 10.3109/00048679709065068
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a New Integrated Mental Health Service on Hospitalisation

Abstract: The hypotheses of this study were supported by the results. Twelve beds were subsequently closed as a result of the efficiencies generated by integration. These findings support the model of true integration trailled here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…In Geelong, the public mental health services are provided by an 'integrated team' approach [10] whereby a single multidisciplinary team of mental health workers is responsible for the care and management of patients both in hospital and in the community. Over a 15-week period, from April to August 1997, staff assessed all inpatients within a few days of admission and again within a few days of discharge using version 4 of the HoNOS [2].…”
Section: Methodsmentioning
confidence: 99%
“…In Geelong, the public mental health services are provided by an 'integrated team' approach [10] whereby a single multidisciplinary team of mental health workers is responsible for the care and management of patients both in hospital and in the community. Over a 15-week period, from April to August 1997, staff assessed all inpatients within a few days of admission and again within a few days of discharge using version 4 of the HoNOS [2].…”
Section: Methodsmentioning
confidence: 99%
“…No randomized controlled trials were identified. There were 13 non-randomized comparative studies which compared outcomes of continuity and specialisation systems [2,1,14,16,19–22,26,27,30,29,31,3638,40], three survey studies which investigated patient and staff views towards continuity and specialisation systems [3,15,35], and one qualitative semi-structured interview study on staff views towards the two systems [17].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 13 non-randomized comparative studies, one was a cluster non-randomized controlled trial (NRT) [16,19] which compared patient outcomes in an assertive community treatment service with continuity across inpatient and outpatient care, to standard care with separate inpatient and outpatient services. One study was a controlled before and after study (CBA) [26] which compared service level data (consisting of separate samples before and after) following the integration of an inpatient ward with outpatient services whilst a control site maintained separate specialised services. Three cohort studies [22,37,38,40] followed patients over time and compared outcomes of those treated in continuity systems and specialisation systems.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations